Stringybarks to orchards : a history of Forest Range and Lenswood - Bishop, Geoffrey C.; Lenswood Cold Stores Co-operative Society (Hawthorndene, S. Aust. : Lenswood Cold Stores Co-operative Society, 1984)
Local history of Forest Range-Lenswood in the Adelaide Hills ; occasional references to Aboriginal inhabitants.
Includes bibliographical references and index.
Keywords: South Australia. Lenswood region, 1849-1983 & Forest Range region, 1849-1983.; Economic sectors - Agriculture and horticulture - Fruit and vegetable; Settlement and contacts - Settlers; Peramangk people (S5) (SA SI54-09); Lenswood Region (S.A.) -- History; Forest Range Region (S.A.) -- History; Mount Lofty Ranges (SE SA SI54-09); Mount Barker (SE SA SI54-13)